Muricholic acid mediates puberty initiation via the hypothalamic TGR5 signaling pathway - Shan Wang; Ke Huang; Ana Liu; Senjie Wang; Runqiu Jiang; Wenlian Chen; Huiying Wang; Rahim Ullah; Chuqing Xue; Wei Wu; Guanping Dong; Peifang Jiang; et al. (Proceedings of the National Academy of Sciences, 2025)
The onset of puberty is increasingly observed at earlier ages in children, especially in girls with obesity, a trend that predisposes them to long-term metabolic and reproductive disorders in adulthood. Bile acids have emerged as pivotal signaling molecules in both metabolic and reproductive disorders, but remain unexplored in the early onset of puberty in children. Herein, we find elevated levels of muricholic acid (MCA) species in the serum of girls with central precocious puberty, which strongly correlate with indices of hypothalamic–pituitary–gonadal axis activation and can reach peak levels during puberty among healthy children. Intriguingly, reduction of MCA species can lead to decreased expression of gonadotropin-releasing hormone (GnRH) and delay the early onset of puberty, while elevated MCA levels induced premature sexual development in female mice. Mechanistically, we demonstrated that MCA had strong activation effects on Takeda G-protein-coupled receptor 5 (TGR5), and MCA enhanced GnRH expression in GnRH neurons through activation of the TGR5-PI3K/Akt-mTOR signaling pathway. Our findings reveal a link between metabolic status and reproductive maturation, highlighting MCA as a potential therapeutic target for managing early puberty initiation.